Analysis The Influence of Trust on Wow With Congruence and Attitudes As Variables Intervening (Case Study on Go-Food Services in the Special Region of Yogyakarta) - Daffa, Muhammad; Hidayat, Anas (Cita konsultindo, 2024)
This study aims to analyze the effect of trust on word of mouth (WOM) with congruence and attitudes as intervening variables, with a case study on Go-Food services in the Special Region of Yogyakarta. In this context, trust is considered the main factor influencing consumer WOM behavior, while congruence (the match between expectations and experiences) and attitudes act as mediators connecting trust with WOM. This study uses a quantitative method with data collection techniques through surveys of Go-Food users in the Special Region of Yogyakarta as many as 340 respondents. The sampling technique uses a non-probability sampling technique using the purposive sampling method which is then processed using the PLS-SEM statistical analysis tool using SmartPLS software version 3.0. The results of the study indicate that trust has a significant positive effect on WOM, both directly and through consumer attitudes as an intervening variable. In addition, congruence is also proven to mediate the relationship between trust and attitudes, which in turn increases the tendency of consumers to share positive experiences about Go-Food services. The implication of this finding is the importance for companies to maintain and increase consumer trust levels, create experiences that match expectations, and build positive customer attitudes to strengthen WOM. This study contributes to the development of consumer relationship-based marketing strategies, especially in the food delivery application service industry.